2007
DOI: 10.1002/ange.200701581
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Total Synthesis of Pinnaic Acid

Abstract: Zusammengebastelt: Die asymmetrische Totalsynthese von Pinnasäure gelang auf einem stereospezifischen Weg, wobei Schlüsselschritte eine Pd‐katalysierte Trimethylenmethan(TMM)‐[3+2]‐Cyclisierung, eine vierstufige Tandem‐Hydrierung‐Cyclisierung und Kreuz‐Olefinmetathesereaktionen waren (siehe Schema).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Since in many published syntheses 10-30 mol % or more of Ru has been used as a default minimal amount, [12] we think that this observation is of great practical value. [16] The first-generation catalysts can still be used as a more economical alternative for metathesis reactions in which dior trisubstituted C=C bonds are formed. [1,12] In some reactions, it has been observed that first-generation catalysts are more selective as compared with their second-generation heirs.…”
Section: Selection Of the Test Reactionsmentioning
confidence: 99%
“…Since in many published syntheses 10-30 mol % or more of Ru has been used as a default minimal amount, [12] we think that this observation is of great practical value. [16] The first-generation catalysts can still be used as a more economical alternative for metathesis reactions in which dior trisubstituted C=C bonds are formed. [1,12] In some reactions, it has been observed that first-generation catalysts are more selective as compared with their second-generation heirs.…”
Section: Selection Of the Test Reactionsmentioning
confidence: 99%
“…In 2007, Uemura's group completed the asymmetric total synthesis of pinnaic acid. 36 Then, they continued this route and completed the enantioselective total synthesis of halichlorine based on early result. In this section, we give a detailed report on this total synthesis route of (+)-halichlorine (Scheme 14).…”
Section: Asymmetric Synthesis Of Halichorinementioning
confidence: 99%
“…In 2007, the Uemura group described a novel strategy for asymmetric total synthesis using Pd-catalyzed trimethylenemethane [3 + 2] cyclization (Pd-TMM cyclization). 36 In 2014, they further optimized this route, which achieved total synthesis of pinnaic acid. 37 Aldehydes were formed by Parkin-Doering oxidation (SO 3 $Py, DMSO) from the key intermediate 14.8 and reacted with phosphonate 25.1 (Horner-Wadsworth-Emmons reaction).…”
Section: Asymmetric Synthesis Of Pinnaic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 In 2004, HEATHCOCK and co-workers reported the total synthesis of the racemates of 4 and 7. 12 Later some other groups published formal total syntheses of these marine alkaloids.…”
Section: Total Syntheses Of Halichlorine and Pinnaic Acidmentioning
confidence: 99%